2018
DOI: 10.1016/j.bbalip.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets enriched in linoleic acid and its peroxidation products on brain fatty acids, oxylipins, and aldehydes in mice

Abstract: A B S T R A C TBackground: Linoleic acid (LA) is abundant in modern industrialized diets. Oxidized LA metabolites (OXLAMs) and reactive aldehydes, such as 4-hydroxy-2-nonenal (4-HNE), are present in heated vegetable oils and can be endogenously synthesized following consumption of dietary LA. OXLAMs have been implicated in cerebellar degeneration in chicks; 4-HNE is linked to neurodegenerative conditions in mammals. It unknown whether increasing dietary LA or OXLAMs alters the levels of oxidized fatty acids (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
3
20
0
2
Order By: Relevance
“…In conclusion, while it has previously been shown that the oxylipin content of the brain can be modified by changes in the composition of a chronically consumed diet [12][13][14][15][16][17], in this study we demonstrate that a single meal exposure is sufficient to produce differences in oxylipin content. We also demonstrate that fasting alters brain oxylipin content.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In conclusion, while it has previously been shown that the oxylipin content of the brain can be modified by changes in the composition of a chronically consumed diet [12][13][14][15][16][17], in this study we demonstrate that a single meal exposure is sufficient to produce differences in oxylipin content. We also demonstrate that fasting alters brain oxylipin content.…”
Section: Discussionsupporting
confidence: 50%
“…In previous work conducted in our laboratory, we found that the consumption of a Western diet over the period of three months increased arachidonic acid derived oxylipins and altered the fatty acid profiles of the brains of mice [12]. Further, others have shown that various modifications of a chronically consumed diet have the potential to modify brain oxylipin levels [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 72%
“…There is limited information on brain LA and OXLAM metabolism in developing rats. In adult mice, brain OXLAM concentrations were increased with dietary LA levels, but were unaffected by feeding oxidized corn oil (enriched with OXLAMs) for 8 weeks (Ramsden et al ). The fact that pup brain LA was the least abundant fatty acid relative to others (not detected or <3% composition in the lipid pools analyzed), while its metabolites constituted approximately half of the measured oxylipins, suggests that LA entering the brain is likely metabolized into OXLAMs instead of being retained.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma non esterified-DHA (NE-DHA) is the main contributor to brain DHA [ 51 , 52 ]. Significantly, LA and EPA are highly represented in the cerebellum, while ARA and DHA are in the cerebrum [ 53 ]. ω-3 PUFAs play a fundamental role in maintaining the membrane integrity and fluidity, which is crucial for neurotransmitter binding, and signaling [ 54 ].…”
Section: Importance Of Pufas In Brain Functioning and Brain Cancermentioning
confidence: 99%